Big Data Review of the Influence of Agricultural Sector Development on Economic Resilience - Dimas Tri Rendra Graha; Revika Fatridica Nurinaputri; Isnaini Salsabilah (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2024)
The agricultural sector in the East Java's GDP structure has been stable at around 11% over the past 5 years, despite disruptions caused by the Covid pandemic. The stable development of the agricultural sector has contributed to the region's increased resilience. This study aims to identify the relationship between factors influencing agricultural development and resilience in East Java and to formulate related development strategies. The method used in this study is Correlation and Regression. Regional resilience is viewed as the output of changes in the rate of GDP growth. Factors in agricultural development are viewed from Agricultural Production, Land Factors using Big data, including LST, NDVI, and NDWI, Internet User Farmers and Farmer Populations. The results of the study indicate that significant influential factors in agricultural development are found in NDVI, NDWI, and Farmer Population. The study shows that for East Java, development strategies through digital farming have not yet been able to increase regional resilience, and conventional agricultural development methods still dominate.